ADR mechanisms to resolve potential disputes on the payment of takaful benefits under conditional hibah - Salleh, Safinar; Halim, Akmal Hidayah; Ibrahim, Uzaimah; Abdullah, Mohamad Asmadi (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
The application of conditional hibah to the rule of nomination for the payment of takaful benefits under the Islamic Financial Services Act (IFSA) 2013 draws certain legal issues. One of the issues relates to the entitlement of any of legal heirs of the deceased takaful participant to challenge the payment of takaful benefits to the nominee(s) under conditional hibah. In addition, the existence of a statutory provision that indirectly prevents such a challenge further complicates the matter. Hence, this paper examines the extent of the legal heirs’ rights to annul such payment and to insist for the distribution of takaful benefits in accordance with the rule of fara’idh (inheritance). The analysis of this study will cover both Islamic law perspective as well as the provision of IFSA 2013. As takaful benefits are meant to provide for the general well-being of those left by the deceased policyholder, the paper predicates that the nomination should be able to be modified to cater the need of at least the policyholder’s dependants who might not be named as the intended beneficiary of the conditional hibah. In this context, the paper proposes that ADR mechanisms such as mediation and negotiation should be applied for the payment of takaful benefits so that the rights of the nominee(s) and the legal heirs are well protected and not adversely affected.